Design, synthesis and theoretical analysis of functionalized dicarboxylate moieties based on organotin(IV) dinuclear complexes: crystal structure elucidation and biological studies. Issue 15 (3rd August 2017) - Shakir, Mohammad; Sharma, Prashant Kumar; Hanif, Summaiya; Ahmad, Musheer
Abstract: Dinuclear tin(IV) dicarboxylate complexes of the types [(n-Bu)2 Sn(oda)(4-pic)]2 ·2H2 O (1 ) and [(n-Bu)2 Sn(pda)(H2 O)]2 (2 )[ H2 oda = oxydiacetic acid; H2 pda = pyridine 2, 6-dicarboxylic acid) were synthesized and characterized via physicochemical and spectroscopic studies. The spectroscopic results indicated that Sn is seven-coordinate having pentagonal bipyramidal (pbp) geometry in both complexes. The X-ray study of complex2 further specified pentagonal bipyramidal geometry with dinuclear structural arrangement due to the involvement of carboxylate bridges formed by pda 2− moiety. The crystal structure is further stabilized by different weak interactions viz., C–C⋯H, C–C⋯O, C–H⋯O, C–C⋯O, and C–H⋯H. These interactions are further supported by Hirshfeld surface analysis along with 2-D fingerprint plots of complex2 . In vitro DNA-binding studies of both complexes were evaluated using spectroscopic techniques (absorbance and fluorescence) which ascertained optimum binding affinity of both complexes. However, cleavage activity of the complexes was assessed using supercoiled DNA (pBR322) via gel electrophoresis technique which demonstrated significant cleavage pattern of both complexes at different concentrations. Furthermore, chemotherapeutic potential of complexes1 and2 against MCF-7 and Hep carcinoma cell lines also suggested significant antiproliferative effect of complexes. These results revealed momentous exploration of drug–DNA interactions which may engender new insinuation for the advancement of metallo-pharmaceuticals. Abstract :